The African Acheulean - Sahnouni, Mohamed; Semaw, Sileshi; Rogers, Michael (The Oxford Handbook of African Archaeology, 2013)
This article argues that the Acheulean is perhaps the longest lasting cultural–technological tradition in human history, dating from around 1.7 to 0.3 Mya and roughly corresponding to the time during which H. Erectus and H. Heidelbergensis lived in Africa. Unlike earlier Oldowan technology, Acheulean cores — handaxes, cleavers, and picks — were standardised, of predetermined shape and made on large cobbles and flakes. The extensive Acheulean archaeological record throughout Africa over 1.4 million years described is testimony to the success of this technology’s makers in different habitats, altitudes, and settings, but also to its apparent conservative cultural nature: a learned tradition passed on through thousands of generations of highly mobile hominin groups with small population sizes. Although there are differences between Early and Late Acheulean technology, the makers of these tools may have undergone more significant changes with respect to the use of other technologies, strategic land use, and social life.
Citation Key Alias: lens.org/025-853-927-978-71X, sahnouniAfricanAcheulean2013
Keywords: dept.ant

Hominin exploitation of animal resources at the Gona Plio-Pleistocene archeological sites (Afar, Ethiopia) - Cáceres, Isabel; Rogers, Michael J.; Semaw, Sileshi; Leiss, Amanda C. (Proceedings of the II meeting of african prehistory - Burgos 15-16 April, 2015 = Actas de las II Jornadas de prehistoria africana, 2017)
tex.crossref: https://zenon.dainst.org/Record/001516034
Keywords: dept.ant; ⛔ No DOI found

Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
157 citations (Crossref) [2023-10-31] tex.ids: ISI:000279276600002, Rogers2010, lens.org/048-194-199-785-52X tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

Archaeology and the origins of human cumulative culture: a case study from the earliest Oldowan at Gona, Ethiopia - Stout, Dietrich; Rogers, Michael J.; Jaeggi, Adrian V.; Semaw, Sileshi (Current Anthropology, 2019)
The capacity of Homo sapiens for the intergenerational accumulation of complex technologies, practices, and beliefs is central to contemporary accounts of human distinctiveness. However, the actual antiquity and evolutionary origins of cumulative culture are not known. Here we propose and exemplify a research program for studying the origins of cumulative culture using archaeological evidence. Our stepwise approach disentangles assessment of the observed fidelity of behavior reproduction from inferences regarding required learning mechanisms (e.g., teaching, imitation) and the explanation of larger-scale patterns of change. It is empirically grounded in technological analysis of artifact assemblages using well-validated experimental models. We demonstrate with a case study using a toolmaking replication experiment to assess evidence of behavior copying across three 2.6 Ma Oldowan sites from Gona, Ethiopia. Results fail to reveal any effects of raw material size, shape, quality, or reduction intensity that could explain the observed details of intersite technological variation in terms of individual learning across different local conditions. This supports the view that relatively detailed copying of toolmaking methods was already a feature of Oldowan technological reproduction at ca. 2.6 Ma. We conclude with a discussion of prospects and implications for further research on the evolution of human cumulative culture.
69 citations (Crossref) [2023-10-31] tex.ids: ISI:000470895900002, Michael_Rogers48838567 tex.eissn: 1537-5382 tex.unique-id: ISI:000470895900002
Keywords: dept.ant; peer-reviewed

The lower limb of Ardipithecus ramidus - Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael; Semaw, Sileshi (American Journal of Physical Anthropology, 2019)
tex.eissn: 1096-8644 tex.organization: Amer Assoc Phys Anthropologists tex.unique-id: ISI:000458409602334 88th Annual Meeting of the American-Association-of-Physical-Anthropologists (AAPA), Cleveland, OH, MAR 27-30, 2019
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Postcranial fossils of Ardipithecus ramidus from Gona, Ethiopia - Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (American Journal of Physical Anthropology, 2018)
tex.eissn: 1096-8644 tex.organization: Amer Assoc Phys Anthropologists tex.unique-id: ISI:000430656804068 87th Annual Meeting of the American-Association-of-Physical-Anthropologists (AAPA), Austin, TX, APR 11-14, 2018
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Ardipithecus ramidus postcrania from the Gona Project area, Afar Regional State, Ethiopia. - Simpson, Scott W; Levin, Naomi E; Quade, Jay; Rogers, Michael J; Semaw, Sileshi (Journal of human evolution, 2019)
Functional analyses of the 4.4 Ma hominin Ardipithecus ramidus postcrania revealed a previously unknown and unpredicted locomotor pattern combining arboreal clambering and a form of terrestrial bipedality. To date, all of the fossil evidence of Ar. ramidus locomotion has been collected from the Aramis area of the Middle Awash Research Project in Ethiopia. Here, we present the results of an analysis of additional early Pliocene Ar. ramidus fossils from the Gona Project study area, Ethiopia, that includes a fragmentary but informative partial skeleton (GWM67/P2) and additional isolated manual remains. While we reinforce the original functional interpretations of Ar. ramidus of having a mixed locomotor adaptation of terrestrial bipedality and arboreal clambering, we broaden our understanding of the nature of its locomotor pattern by documenting better the function of the hip, ankle, and foot. The newly recovered fossils document a greater adaptation to bipedality in the Ar. ramidus ankle and hallux than previously recognized. In addition, a newly discovered scaphoid bone with a fusing os centrale provides further evidence about the nature of hominin hand evolution. Copyright © 2018 Elsevier Ltd. All rights reserved.
26 citations (Crossref) [2023-10-31] Place: England Simpson, Scott W. Department of Anatomy, Case Western Reserve University School of Medicine, Cleveland, OH 44106-4930, USA; Institute for the Science of Origins, Case Western Reserve University, Cleveland, OH 44106, USA; Laboratory of Physical Anthropology, Cleveland Museum of Natural History, Cleveland, OH 44106, USA. Electronic address: sws3@cwru.edu. Levin, Naomi E. Department of Earth and Environmental Sciences, University of Michigan, Ann Arbor, MI 48109, USA. Electronic address: nelevin@umich.edu. Quade, Jay. Department of Geosciences, University of Arizona, Tucson, AZ 85721, USA. Electronic address: quadej@email.arizona.edu. Rogers, Michael J. Department of Anthropology, Southern Connecticut State University, New Haven, CT 06515, USA. Electronic address: rogersm1@southernct.edu. Semaw, Sileshi. Centro Nacional de Investigacion Sobre La Evolucion Humana (CENIEH), Sierra de Atapuerca 3, 09002, Burgos, Spain; The Stone Age Institute, 1392 West Dittemore Road, Gosport, IN 47433, USA; CRAFT, Indiana University, Bloomington, IN 47405, USA. Electronic address: sileshi.semaw@CENIEH.es.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Hominidae/ph [Physiology]; *Locomotion; Adaptation; Biological; Afar; Animals; Ardipithecus ramidus; Biological Evolution; Bipedality; Ethiopia; Fossils; Gona; Hominidae; Hominin; Locomotion; Pliocene; Postcrania; Skeleton; Skeleton/ah [Anatomy & Histology]; adaptation; anatomy and histology; animal; bipedalism; bone; cranium; dept.ant; evolution; fossil; hominid; locomotion; paleontology; peer-reviewed; physiology; skeleton

The Early Acheulean ~1.6–1.2 Ma from Gona, Ethiopia: Issues related to the emergence of the Acheulean in Africa - Semaw, Sileshi; Rogers, Michael J.; Cáceres, Isabel; Stout, Dietrich; Leiss, Amanda C. (The Emergence of the Acheulean in East Africa and Beyond: Contributions in Honor of Jean Chavaillon, 2018)
Konso in Ethiopia and Kokiselei in Kenya, both dated to ~1.7 million years ago (Ma), and FLK West, a recently reported site from Olduvai dated to 1.7 Ma, are the earliest Acheulean sites known in East Africa. Ongoing archaeological investigations at Gona, in the Afar Depression of Ethiopia, have also produced early Acheulean stone assemblages at several sites, estimated to ~1.6–1.2 Ma. A number of sites, including BSN-12 and OGS-12, have yielded archaeological materials comparable to the earliest Konso artifacts. The stone assemblages from the Gona sites consist of crudely made handaxes, cleavers, and picks, as well as Mode I (Oldowan) cores, and débitage. A variety of raw materials were exploited at Gona, with trachyte, rhyolite, and basalt being the most common.Our understanding of the behavioral and ecological background for the emergence of the Acheulean is still limited. Preliminary comparisons of BSN-12 and OGS-12 with other early Acheulean sites demonstrate variability in paleoecological settings as well as raw material use. Current archaeological evidence indicates that early Homo erectus/ergaster use of this new technology was already in place in East Africa ~1.75 Ma. At Gona and elsewhere in Africa, continued survey and excavations are needed to document sites with potential for yielding archaeological traces that will help our understanding of the Oldowan–Acheulean transition, the identity of the toolmakers, and the function of the early Acheulean Large Cutting Tools (LCTs).
Citation Key Alias: lens.org/010-344-387-916-971
Keywords: Ethiopia; Gona; Oldowan–Acheulean transition; Technical behaviors; dept.ant

Gona - Semaw, Sileshi; Rogers, Michael J. (The International Encyclopedia of Biological Anthropology, 2018)
tex.ids: semawGona2018a
Keywords: dept.ant

Late Miocene hominin teeth from the Gona Paleoanthropological Research Project area, Afar, Ethiopia. - Simpson, Scott W; Kleinsasser, Lynnette; Quade, Jay; Levin, Naomi E; McIntosh, William C; Dunbar, Nelia; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2015)
Since 2000, significant collections of Latest Miocene hominin fossils have been recovered from Chad, Kenya, and Ethiopia. These fossils have provided a better understanding of earliest hominin biology and context. Here, we describe five hominin teeth from two periods (ca. 5.4 Million-years-ago and ca. 6.3 Ma) that were recovered from the Adu-Asa Formation in the Gona Paleoanthropological Research Project area in the Afar, Ethiopia that we assign to either Hominina, gen. et sp. indet. or Ardipithecus kadabba. These specimens are compared with extant African ape and other Latest Miocene and Early Pliocene hominin teeth. The derived morphology of the large, non-sectorial maxillary canine and mandibular third premolar links them with later hominins and they are phenetically distinguishable and thus phyletically distinct from extant apes. Copyright © 2014 Elsevier Ltd. All rights reserved.
22 citations (Crossref) [2023-10-31] Place: England Simpson, Scott W. Department of Anatomy, Case Western Reserve University School of Medicine, Cleveland, OH 44106-4930, USA; Institute for the Science of Origins, Case Western Reserve University, Cleveland, OH 44106, USA; Laboratory of Physical Anthropology, Cleveland Museum of Natural History, Cleveland, OH 44106, USA. Electronic address: sws3@cwru.edu. Kleinsasser, Lynnette. Department of Geosciences, University of Arizona, Tucson, AZ 85721, USA; Barrick Cortez, HC 66 Box 1250, Crescent Valley, NV 89821 USA. Electronic address: lkleinsasser@barrick.com. Quade, Jay. Department of Geosciences, University of Arizona, Tucson, AZ 85721, USA. Electronic address: quadej@email.arizona.edu. Levin, Naomi E. Department of Earth & Planetary Sciences, Johns Hopkins University, Baltimore, MD 21218, USA. Electronic address: nlevin3@jhu.edu. McIntosh, William C. New Mexico Bureau of Geology and Mineral Resources & Department of Environmental Science, New Mexico Institute of Mining and Technology, Socorro, NM 87801, USA. Electronic address: mcintosh@nmt.edu. Dunbar, Nelia. Department of Environmental Science, New Mexico Institute of Mining and Technology, Socorro, NM 87801, USA. Electronic address: nelia@nmt.edu. Semaw, Sileshi. Centro Nacional de Investigacion sobre la Evolucion Humana (CENIEH), Paseo Sierro de Atapuerca 3, Burgos 09002, Spain; The Stone Age Institute, 1392 West Dittemore Road, Gosport, IN 47433, USA; CRAFT, Indiana University, Bloomington, IN 47405, USA. Electronic address: Sileshi.semaw@cenieh.es. Rogers, Michael J. Department of Anthropology, Southern Connecticut State University, New Haven, CT 06515, USA. Electronic address: rogersm1@southernct.edu.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Tooth/ah [Anatomy & Histology]; Afar; Animals; Ardipithecus; Ardipithecus kadabba; Ardipithecus ramidus; Biological Evolution; Ethiopia; Fossils; Hominidae; Hominina; Late miocene; Miocene; Orrorin; Tooth; Western ethiopian escarpment; anatomy and histology; animal; anthropology; canid; dept.ant; evolution; fossil; hominid; morphology; peer-reviewed; tooth

The first technical sequences in human evolution from East Gona, Afar region, Ethiopia - de Lumley, Henry; Barsky, Deborah; Moncel, Marie Hélène; Carbonell, Eudald; Cauche, Dominique; Celiberti, Vincenzo; Notter, Olivier; Pleurdeau, David; Hong, Mi-Young; Rogers, Michael J.; Semaw, Sileshi (Antiquity, 2018)
Gona in the Afar region of Ethiopia has yielded the earliest Oldowan stone tools in the world. Artefacts from the East Gona (EG) 10 site date back 2.6 million years. Analysis of the lithic assemblage from EG 10 reveals the earliest-known evidence for refitting and conjoining stone artefacts. This new information supplements data from other Oldowan sites in East Africa, and provides an important insight into the technological capacities and evolutionary development of hominins during this period.
7 citations (Crossref) [2023-10-31] tex.ids: ISI:000448528600012, Rogers2018 tex.eissn: 1745-1744 tex.orcid-numbers: Barsky, Deborah/0000-0002-4921-0389 tex.researcherid-numbers: Barsky, Deborah R/L-5468-2014 tex.unique-id: ISI:000448528600012
Keywords: East Gona; Ethiopia; Oldowan; dept.ant; knapping; peer-reviewed; refitting